Biodiversity assessment of Eucyclops Claus, 1893 (Copepoda: Crustacea) in the Baikal region using genetic methods - Tatyana Yu. Mayor; Olga A. Chaban; Kseniia A. Kaskova; Natalia M. Sukhikh (Acta Biologica Sibirica)
The genus Eucyclops is the most species-rich within the subfamily Eucyclopinae. Despite the significant research of Eucyclops in Russia, there are still vast areas including Siberia, the Baikal region, and the Far East with fragmentary study of this genus, particular with regard to molecular methods. In this work we have sequenced four molecular markers with different evolutionary rates and inheritance types (COI and 12S rRNA mtDNA, 18S rRNA and ITSn rDNA) to estimate the biodiversity of Eucyclops in the Baikal region. Five species E. serrulatus, E. speratus, E. macruroides, E. arcanus, and E. macrurus baicalocorrepus were identified through a combination of morphological and genetic methods in the Baikal region. The necessity for a taxonomic revision of endemic Baikal E. macrurus baicalocorrepus and E. macruroides baicalensis has been established. We assume that two forms of E. macrurus baicalocorrepus with short and long caudal rami are distinct endemic Baikal species. The genetic analysis of E. serrulatus, E. speratus, and E. macruroides revealed that the Baikal Cyclopoida, along with the Far Eastern and other Siberian representatives of the genus, form a distinct genetic lineage that differs from the majority of European representatives, with some exceptions.